Shaping the future of the Hotel Sectot through consortia: the portuguese case - Almeida, Sofia (2021)
Networks are cooperation arrangements that have gained importance over the last century. In the future, network-based and network structures will be among the most important organizational models. Therefore, this assumption formed the basis of the questionnaire designed for conducting this research. The objectives of this research are: (1) to examine hotel decision-makers’ perceptions about the future of networks in tourism and (2) to analyse the influence of online distribution on hotel marketing consortia. A questionnaire was sent to four- and five-star hotel units in Portugal. Quantitative and qualitative data analysis was performed. Main conclusions and recommendations for both academics and practitioners are then presented and discussed.